Self-management program impact on type 2 diabetes blood sugar control - Kawthaisong, Chontira; Wongsricha, Parichat; Machara, Charinporn (Intelektual Pustaka Media Utama, 2025)
Type 2 diabetes mellitus (DM) represents a major global public health concern. This quasi-experimental study assessed the effectiveness of a self-management program in aiding diabetic patients in controlling their blood sugar levels. The program implemented the self-management framework proposed by Kanfer and Gaelick-Buys, supplemented by social support from healthcare volunteers via home visits. Patients were selected through simple random sampling and subsequently divided into two groups, each comprising 30 patients. The experimental group received a self-management program, with progress monitored over a 12-week period. The control group was administered standard care. The Mann-Whitney U test and the Wilcoxon signed-rank test were employed to assess the data. The results indicated that the self-management behavior and blood sugar levels of both the experimental and control groups were similar before the experiment commenced. Significant differences were observed in self-management behavior and blood sugar levels between the experimental groups before and after the intervention, as indicated by a significance level of 0.05. However, this program has some limitations, including the fact that the evaluation did not include HbA1c levels, and the data was based on participants' self-reports, which may be subject to bias. The finding suggests that this self-management program can be implemented by healthcare professionals in the community to effectively manage blood sugar levels among type 2 diabetes patients to reduce the incidence of complications, with rigorous and continuous monitoring of behaviors required.